Analysis of STEAM Learning in Developing the Creativity of Children Aged 4–5 Years - Khuriyah Ilmi Haqiqi; Renistiara Medilianasari (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2026)
This study aims to describe the process of STEAM-based learning in developing the creativity of children aged 4–5 years at PAUD Sekar Nagari. This study employed a descriptive qualitative approach using a case study method. The research participants consisted of 20 children, 2 classroom teachers, and the school principal. Data were collected through observations, interviews, and documentation. The findings indicate that STEAM learning was implemented through play-based activities integrating the elements of science, technology, engineering, arts, and mathematics into thematic learning activities. The learning process consisted of the stages of apperception, stimulation, exploration, and reflection. Teachers acted as facilitators by providing children with opportunities to explore, experiment, and freely express their ideas. STEAM learning was able to develop children's creativity, as reflected in their ability to generate diverse ideas, solve problems using various approaches, and create unique and imaginative works. Although several challenges were encountered, such as limited time and learning media, the learning process remained effective through the utilization of simple materials available in the surrounding environment.